Prevalence of suicidal behavior in young university students: A systematic review with meta-analysis - Marília de Oliveira Crispim; Cândida Maria Rodrigues dos Santos; Iracema da Silva Frazão; Cecília Maria Farias de Queiroz Frazão; Rossana Carla Rameh de Albuquerque; Jaqueline Galdino Albuquerque Perrelli (Universidade de São Paulo, 2021)
Objective: to identify the prevalence of suicidal behavior in young university students. Method: a systematic review with meta-analysis of cross-sectional studies based on the Joanna Briggs Institute proposal, and carried out in the PubMed, Web of Science, Scopus, PsycINFO and LILACS databases and in the Brazilian Digital Library of Theses and Dissertations, with no language or year restrictions. A total of 2,942 publications were identified. Selection, data extraction and methodological evaluation of the studies were performed by two independent researchers. The meta-analysis was performed considering the random effects model. Results: eleven articles were included in this review. The prevalence variation for suicidal ideation was from 9.7% to 58.3% and, for attempted suicide, it was from 0.7% to 14.7%. The meta-analysis showed a 27.1% prevalence for suicidal ideation in life, 14.1% for ideation in the last year, and 3.1% for attempted suicide in life. Conclusion: the high prevalence of suicidal behavior, even with the considerable heterogeneity of the studies, raises the need to implement interventions aimed at preventing suicide and promoting mental health, especially in the academic environment.